Correction: Implications for the Prevention of Poverty-Related Environmental Risks for Childhood ADHD: A Narrative Review. - İçen, Sarper (Child Psychiatry & Human Development, 2026)
This correction notice addresses errors in the reference list of an article originally published on child psychiatry and human development. Specifically, while the in-text citations were correctly numbered, the corresponding entries in the reference list were not in the proper numerical order. The publisher has updated the original article to correct the reference list, ensuring alignment between in-text citations and reference entries. The notice also includes a standard disclaimer regarding the publisher's neutrality on jurisdictional claims.